Agresywne zachowania uczniów ze SPE jako źródła lęków nauczycieli. Korelacja osłabiająca sukces edukacji włączającej - Baranowska, Wanda; Leszka, Justyna (Studia Edukacyjne, 2021)
In inclusive education, teachers work with all students, including those exhibiting aggressive behaviors. Today, many teachers struggle with challenging student behavior. The study aims to examine (1) aggressive behaviors in students with SPE – a source of teacher frustration in inclusive education, (2) the consequences of these behaviors triggering fears in teachers, and (3) the relationship between teacher seniority and likely consequences as per objective 2. The survey was conducted among 188 teachers. The data were analyzed using descriptive and correlational approaches. We determined that (1) the main source of teacher frustration is the physical aggression displayed by students with ASD, ADHD, ODD and CD; (2) the fear students with SEN may hurt other students is prominent amongst teachers, with a linear correlation between predictable consequences, where the strongest links appear between prediction of conflict in a classroom and the accusation of incompetence levelled at teachers by parents of students with SEN and between the fear of losing self-control and disapproval by superiors; (3) no significant relationship exists between the seniority of teachers and their perception of the sources of frustrations and fears. Against the background of the results, we formulated recommendations on inclusive education training for teachers.